Nonlinearities of the Sabotage-Redistribution Process - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2014)
The relationship between sabotage and redistribution is inherently nonlinear. This research note illustrates aspects of this nolinearity in the case of the United States.
Keywords: 330; sabotage; redistribution; United States